Comparison of antegrade continence enema treatment and sacral nerve stimulation for children with severe functional constipation and fecal incontinence. Issue 8 (3rd February 2020) - Vriesman, Mana H.; Wang, Lyon; Park, Candice; Diefenbach, Karen A.; Levitt, Marc A.; Wood, Richard J.; Alpert, Seth A.; Benninga, Marc A.; Vaz, Karla; Yacob, Desale; Di Lorenzo, Carlo; Lu, Peter L.
Abstract: Background: To compare antegrade continence enema (ACE) treatment and sacral nerve stimulation (SNS) in children with intractable functional constipation (FC) and fecal incontinence (FI). Methods: We performed a retrospective review of children 6‐18 years old with FC and FI treated with either ACE or SNS at our institution. We recorded symptoms at baseline, 6 months, 12 months, 24 months, and their most recent visit after starting treatment. We compared improvement in FI, bowel movement (BM) frequency, abdominal pain, laxative use, and complications. Patients were contacted to evaluate perceived benefit using the Glasgow Children's Benefit Inventory. Key Results: We included 23 patients treated with ACE (52% female, median age 10 years) and 19 patients treated with SNS (74% female, median age 10 years). Improvement in FI was greater with SNS than ACE at 12 months (92.9% vs 57.1%, P  = .03) and 24 months (100% vs 57.1%, P  = .02). Improvement in BM frequency was greater with ACE, and children were more likely to discontinue laxatives at all follow‐up time points (all P  < .05). Improvement in abdominal pain was greater with ACE at the most recent visit ( P  < .05). Rate of complications requiring surgery was similar between groups (26.3% vs 21.7%). Benefit was reported in 83.3% and 100% of ACE and SNS groups, respectively (NS). Conclusions and Inferences: Although both ACE and SNS can lead to durable improvement in children with FC and FI, SNS appears more effective for FI and ACE more effective in improving BM frequency and abdominal pain and in discontinuation of laxatives. Abstract : Follow‐up data was available for 41 children at 6 months after treatment, 35 children at 12 months, 26 children at 24 months and all 42 children at most recent follow‐up. p‐value refers to difference in improvement from baseline. *p<0.05.